Label-free nanoscale ZnO tetrapod-based transducers for tetracycline detection - Brás, M. (2023)
Antibiotic pollution of freshwaters and even food products has become an important concern worldwide. Hence, it is of utmost importance to develop cost-effective and reliable devices that can provide information on the presence of such contaminants to the general population. In the present work, zinc oxide (ZnO) nanotetrapods (NTP) produced via a high yield laser processing approach were used as transducers in a luminescent-based immunosensor to detect tetracycline (TC). These tetrapodal structures present needle-shaped branches with a high aspect ratio, exhibiting lengths from hundreds of nanometers to a few micrometers and an average thickness of tens of nanometers, providing a high surface area for bioreceptor immobilization and analyte reaction, which is quite desirable in a transducer material. Besides, these ZnO NTP display intense photoluminescence (PL) at room temperature, making such a signal rather promising for transduction. Indeed, the intensity of the ZnO PL signal was seen to correlate with the TC concentration. The PL quenching with increasing analyte concentration is explained considering the rise in the bending of the electronic bands of the semiconductor near its surface due to increased charge density at this region, induced by the interaction between the bioreceptor (anti-TC antibodies) and the TC molecules. As a larger depletion width (and potential barrier) is promoted near the surface, the excitonic recombination probability is reduced and, consequently, the PL intensity in the ultraviolet spectral region, allowing us to use this relationship as a sensing mechanism. This information enabled us to define a calibration curve for TC quantification in the 0.001 to 1 μg L–1 range, which is the range of interest of this antibiotic in freshwaters. A limit of detection (LOD) of ∼1.2 ng L–1 is reported, corresponding to one of the lowest LOD found in the literature for this antibiotic, indicating that the present ZnO NTP-based biosensors rival the current state-of-the-art ones.